In situ investigation of mesoporous silicon oxidation kinetics using infrared emittance spectroscopy. Issue 27 (22nd June 2016) - Bardet, Benjamin; De Sousa Meneses, Domingos; Defforge, Thomas; Billoué, Jérôme; Gautier, Gaël
Abstract : The kinetics of mesoporous silicon oxidation is investigated by means of infrared emittance measurements. The chemical mechanisms are put in perspective with temperature. Abstract : In this paper, we study the thermal oxidation kinetics of mesoporous silicon layers, synthesized by electrochemical anodization, from 260 °C up to 1100 °C. A specific apparatus is employed to heat the mesoporous samples in air and to record at the same time their infrared emittance. Based on Bruggeman effective medium approximation, an optical model is set up to realistically approximate the dielectric function of the porous material with an emphasis on the surface chemistry and oxide content. A transition temperature of 600 °C is evidenced from data processing which gives evidence of two oxidation mechanisms with distinct kinetics. Between 260–600 °C, the oxidation is surface-limited with kinetics dependent on the hydrogen desorption rate. However, above 600 °C, the oxide growth is limited by oxygen diffusion through the existing oxide layer. A parabolic law is employed to fit the oxidation rate and to extract the high-temperature activation energy ( E A = 1.5 eV). A precise control of the oxide growth can thus be achieved.